Learning curve for double-balloon enteroscopy: findings from an analysis of 282 procedures - Tee, Hoi Poh; How, Soon Hin; Arthur J., Kaffes (Baishideng Publishing Group, 2012)
AIM: To determine the learning curves for antegrade double-balloon enteroscopy (aDBE) and retrograde DBE (rDBE) by analyzing the technical success rates. METHODS: A retrospective analysis in a tertiary referral center. This study reviewed all cases from June 2006 to April 2011 with a target lesion in the small-bowel identified by either capsule endoscopy or computed tomography scan posted for DBE examinations. Main outcome measurements were: (1) Technical success of aDBE defined by finding or excluding a target lesion after achieving sufficient length of small bowel intubation; and (2) Technical success for rDBE was defined by either finding the target lesion or achieving stable overtube placement in the ileum. RESULTS: Two hundred and eighty two procedures fulfilled the inclusion criteria and were analyzed. These procedures were analyzed by blocks of 30 cases. There was no distinct learning curve for aDBE. Technical success rates for rDBE continued to rise over time, although on logistic regression analysis testing for trend, there was no significance (P = 0.09). The odds of success increased by a factor of 1.73 (95% CI: 0.93-3.22) for rDBE. For these data, it was estimated that at least 30-35 cases of rDBE under supervision were needed to achieve a good technical success of more than 75%. CONCLUSION: There was no learning curve for aDBE. Technical success continued to increase over time for rDBE, although a learning curve could not be proven statistically. Approximately 30-35 cases of rDBE will be required for stable overtube intubation in ileum.